(untitled) (E Global Congress, 2025)
The article analyzes the role and significance of retail banking services in shaping the income of bank service centers. In the modern financial market, as banks strive to diversify their sources of income through digital technologies and customer-oriented services, retail services emerge as the main factor ensuring stable profitability and liquidity.